Sosialisasi dan Pendampingan Pembuatan Nomor Induk Berusaha (NIB) dalam Rangka Pengembangan UMKM Kelurahan Ngipik, Kabupaten Gresik - Pratiwi, Rini; Kusumasari, Indah Respati (Jurnal Bisnis Indonesia, 2024)
These businesses underestimate the legality of the business on the grounds that even without legalitythe business they run is fine and still has buyers. According to them, the legality of the business has noeffect on sales. Because the majority of MSME in Ngipik Village do not yet understand the existence ofa Business Identification Number (NIB) for business legality. Case study and direct practice are themethods used in this service activity which was carried out at the NIB Post activity to assist in makingNIB UMKM. The results of this NIB assistance activity are able to improve the abilities and skills ofKlampok Village residents, especially business actors, regarding the importance of NIB in increasingeconomic resilience and faster and safer business development in terms of business legality. The NIBPost activities organized by the MBKM Village Development KKN group, Ngipik Gresik Village,which were carried out at the Ngipik Village Office, have gone according to plan, namely theawareness of MSME players regarding business ownership which will have a positive impact on theirbusiness in the future.Keywords: Business Legality; MSME; Business Identification Number